1975
DOI: 10.1136/jech.29.4.228
|View full text |Cite
|
Sign up to set email alerts
|

Asthma in schoolchildren. Demographic associations and peak expiratory flow rates compared in children with bronchitis.

Abstract: . Asthma in schoolchildren. The frequency of asthma in 10 971 schoolchildren between the ages of 5 and 14 years was reported by their parents to be 3 8%. Of these, 20'7% were said to have had bronchitis, 5 9% pneumonia, and 4 7% eczema. Asthma was reported more commonly in boys than girls and was greatest in children of social classes I and II. One-third of the children were reported to have had their first attack before the age of 2 years. Few (18 %) first attacks started after the age of 5 years. There was n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

1990
1990
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…Indeed, this appears to be the case, with an increased frequency of allergic diseases in higher socioeconomic groups. A number of studies over the last few decades have reported a greater prevalence of asthma in higher socioeconomic groups [25,51,52]. Some of these studies have been criticised because children with asthma may have been misclassified as wheezy bronchitis.…”
Section: Socioeconomic Status Dietary Fat and Asthmamentioning
confidence: 99%
“…Indeed, this appears to be the case, with an increased frequency of allergic diseases in higher socioeconomic groups. A number of studies over the last few decades have reported a greater prevalence of asthma in higher socioeconomic groups [25,51,52]. Some of these studies have been criticised because children with asthma may have been misclassified as wheezy bronchitis.…”
Section: Socioeconomic Status Dietary Fat and Asthmamentioning
confidence: 99%
“…[93][94][95][96][97] Such results may depend both on how socio-economic status is measured and on the specific outcome examined. Some studies have reported associations of lower socio-economic status with greater airway obstruction and symptoms but not with a diagnosis of asthma.…”
Section: Socio-economic Statusmentioning
confidence: 99%
“…5 11 This may be to a certain extent because of the analytical difficulty of distinguishing birth order from family size. Secondly, it is puzzling that studies based on data collected long ago showed no association between family size and asthma or wheeze [14][15][16][17] while more recent data tend to show an association with both. 7 9 11 In the study of Davis and Bulpitt the lack of association was not restricted to asthma, but observed also for atopy.…”
mentioning
confidence: 99%